Femtosecond nonadiabatic cascade and subsequent photofragmentation of XUV excited caffeine molecule. Issue 14 (January 2020) - Yamazaki, K; Marciniak, A; Maeda, S; Reduzzi, M; Despré, V; Hervé, M; Meziane, M; Niehaus, T; Loriot, V; Kuleff, A; Schindler, B; Compagnon, I; et al.
Synopsis: We found that the XUV excited caffeine undergoes nondadabatic cascade via more than 100 shake-up states within the time constant of 40 fs by using femtosecond XUV-NIR pump-probe photo-ion spectroscopy and the SAC-CI level of ab-initio many-body theory. This nonadiabatic cascade results in the photofragmentation to specific large fragments. Furether ionization by NIR probe during the cascade increases the small fragments CH3 +, CO + etc. This results show that both vibronic coupling and electron correlation are the keys for the femtochemistry in the highly-correlated electronic excited states.